HUMAN RESOURCE DIGITAL COMPETENCY STRATEGIES FOR DIGITAL TRANSFORMATION AT THE MESUJI COMMUNICATION AND INFORMATICS OFFICE - Aura Velian Dasari; V. Saptarini (International Journal of Multidisciplinary Reseach, 2026)
Digital transformation in local government requires not only adequate information technology infrastructure but also public employees who possess relevant and continuously updated digital competencies. This study aims to analyze strategies for strengthening the digital competence of human resources and to identify the constraints encountered at the Communication and Informatics Office of Mesuji Regency. A descriptive qualitative approach was employed. Data were collected through observation, semi-structured interviews with five key informants, documentation, and a literature review. Data validity was examined through source and technique triangulation, prolonged engagement, and persistent observation, while the data were analyzed through data reduction, data display, and conclusion drawing/verification. The findings show that the main strategies consist of education and training, competency-based promotion, and job rotation. These strategies are reinforced through continuous learning, knowledge sharing, mentoring, and digital competency mapping. Their implementation has improved employees' ability to use government applications, manage digital data, and support the Electronic-Based Government System. However, uneven competencies, discontinuous training, the absence of comprehensive competency mapping, limited budgets, and varying adaptability remain major constraints. An integrated and sustainable competency management policy is therefore essential to accelerate digital transformation and improve public service quality.